An old approach to a novel problem: effect of combined balance therapy on virtual reality induced motion sickness: a randomized, placebo controlled, double-blinded study - Kurul Ramazan; Altuntas Yasin Devran; Ogun Nur Muhammed (BMC Medical Education, 2024)
Abstract Background The objective of this study was to investigate the impact of a rehabilitation program aimed at addressing vestibular and proprioceptive deficits, which are believed to underlie the pathophysiology of motion sickness. Methods A total of 121 medical students with motion sickness participated in this study and were randomly divided into intervention (n = 60) and placebo control (n = 61) groups. The intervention group underwent combined balance, proprioception, and vestibular training three times a week for 4 weeks, while the control group received placebo training. The study assessed various measurements, including the Virtual reality sickness questionnaire (VRSQ), tolerance duration, enjoyment level measured by VAS, stability levels using Biodex, and balance with the Flamingo balance test (FBT). All measurements were conducted both at baseline and 4 weeks later. Results There was no significant difference in pre-test scores between the intervention and control groups, suggesting a similar baseline in both groups (p > 0.05). The results showed a significant improvement in VRSQ, tolerance duration, VAS, Biodex, and FBT scores in the intervention group (p < 0.05). While, the control group showed a significant increase only in VAS scores after 4 weeks of training (p < 0.05). A statistically significant improvement was found between the groups for VRSQ (p < 0.001), tolerance duration (p < 0.001), VAS (p < 0.001), Biodex (p = 0.015), and FBT scores (p < 0.05), in favor of the intervention group. Conclusions A combined balance training program for motion sickness proves to be effective in reducing motion sickness symptoms, enhancing user enjoyment, and extending the usage duration of virtual reality devices while improving balance and stability. In contrast, placebo training did not alter motion sickness levels. These findings offer valuable insights for expanding the usage of virtual reality, making it accessible to a broader population.